Three dimensional visualization of subcellular and suborganellar structures in near-native plant cells by synchrotron soft X-ray tomography - Hua, Mo Da-Sang; Lin, Yi-Hung; Hsieh, Chia-Chun; Chen, Chang-Lin; Lin, Zi-Jing (Frontiers in Plant Science, 2025)
Significant advances in photosynthesis research have been achieved using reverse genetics alongside cellular imaging techniques such as confocal microscopy and transmission or scanning electron microscopy. However, these conventional imaging methods often require chemical fixation or physical sectioning, which can alter the native endocellular ultrastructure and limit the ability to observe subcellular environments. In this study, we utilized synchrotron-based soft X-ray tomography (SXT) at the TPS-24A1 beamline of the National Synchrotron Radiation Research Center (NSRRC), Taiwan, to non-destructively visualize three-dimensional ultrastructure of protoplasts isolated from Arabidopsis thaliana and Bidens pilosa in their near-native state. Our results revealed marked differences in organelle morphology and spatial arrangement compared to traditional electron micrographs and confocal images, highlighting the robustness and volumetric resolution of SXT for near-native structural analysis. Importantly, this method enabled visualization of organelles and sub-organelle compartments such as chloroplast thylakoid systems and lipid bodies without chemical fixation or staining. The discovery of previously unreported large vesicular structures in B. pilosa chloroplasts further demonstrates the power of SXT in uncovering novel species-specific ultrastructural features. Overall, this combined approach of protoplast isolation and cryogenic SXT offers a powerful tool for advancing our understanding of photosynthetic machinery and cellular organization. Moreover, it opens new opportunities for studying plant-microorganism interactions, metal uptake, and intracellular biochemical dynamics with minimal sample perturbation.